Cendawan Patogen pada Beberapa Varietas Jagung di Kabupaten Timor Tengah Utara - Albertus Hausufa; Aloysius Rusae (Savana Cendana, 2018)
Corn (Zea mays L.) is an important food because corn is the second source of carbohydrates after rice. Seeds are one of the important components in the successful increase of agricultural production. This study aims to determine the type of fungi associated to corn seed (Zea mays L.) conducted from April to May 2017 at the faculty of agriculture, Timor University. Using Completely Randomized Design (RAL) Factorials and methods used are sampling, observation and pathogen identification performed by morphological characterization, Seedling power testing and maximum growth potential by the UKDdp method. The seeds used are small white local varieties, large white local varieties and hybrids, derived from several localities based on the locality of Eban 1000 meters above sea level, Mamsena 400-800 meters above sea level, Wini 100-200 meters above sea level. The results of identification were obtained by two genera of Aspergillus sp1, Aspergillus sp2, Aspergillus sp3 and Fusarium sp, Aspergillus sp1 highest fungal attack on small local varieties 7.78% and height of place T2 (Wini), Fusarium sp highest on hybrid corn varieties 40.00% and height of the highest place on T1 (Eban) 8.67%. The test of seed germination in the three varieties ranged between 16.44% -26.00%.